Temporal variation of dominant stony coral species in reefs of the Jardines de la Reina National Park, Cuba - Hernández-Fernández, Leslie (2021)
In the Caribbean, coral reefs have been changing constantly as a result of local and global impacts. These changes are also expected to occur in the Jardines de la Reina National Park. The work described here has been carried out to analyze the temporal variation of populations of the dominant groups S. siderea, Orbicella spp., A. agaricites and P. astreoides during 2001, 2012 and 2017, which have been found to have changed in other reefs of Cuba and the Caribbean. During 2001 and 2012 14 sites were surveyed in 88 transects every year, and during 2017 at 24 sites in 240 transects. In 2001, the AGRRA methodology was used; in 2012 and 2017, a new version of this methodology was applied. Six thousand five hundred and one (6,501) colonies were counted and 35 species were identified. S. siderea had an abundance (P = 0.6861) and density (P = 0.0712) which did not vary significantly between the different surveys. The abundance and density of Orbicella spp. decreased between 2001 (24% - 3.2 colonies 10 m-1), 2012 (14% - 1.4 colonies 10 m-1), and 2017 (13% - 1.9 colonies 10 m-1). The abundance of A. agaricites also did not vary significantly between the different surveys (P = 0.2202), while its density increased (2001-2012: 1.4 colonies 10 m-1, 2017: 2 colonies 10 m-1). The abundance of P. astreoides increased (2001: 8%, 2012: 10%, 2017: 12%) as did its density (2001- 2012: 1 colony 10 m-1, 2017: 1.7 colonies 10 m-1). The coral S. siderea prevailed in the reefs, and Orbicella spp. underwent a reduction that caused temporal variation with a displacement toward A. agaricites and P. astreoides.